The genetic stock structure and distribution of Chrysoblephus Puniceus, a commercially important transboundary linefish species, endemic to the South West Indian Ocean - Duncan, Murray Ian (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
Chrysoblephus puniceus is an over-exploited linefish species, endemic to the coastlines off southern Mozambique and eastern South Africa. Over-exploitation and habitat loss are two of the biggest threats to the sustainability of fisheries globally. Assessing the genetic stock structure (a prerequisite for effective management) and predicting climate related range changes will provide a better understanding of these threats to C. puniceus which can be used to improve the sustainability of the fishery. Two hundred and eighty four genetic samples were collected from eight sampling sites between Ponta da Barra in Mozambique and Coffee Bay in South Africa. The mitochondrial control region and ten microsatellite loci were amplified to analyse the stock structure of C. puniceus. The majority of microsatellite and mtDNA pairwise population comparisons were not significant (P > 0.05) although Xai Xai and Inhaca populations had some significant population comparisons for mtDNA (P < 0.05). AMOVA did not explain any significant variation at the between groups hierarchical level for any pre-defined groupings except for a mtDNA grouping which separated out Xai Xai and Inhaca from other sampling sites. SAMOVA, isolation by distance tests, structure analysis, principle component analysis and spatial autocorrelation analysis all indicated a single population of C. puniceus as being most likely. The migrate-n analysis provided evidence of current driven larval transport, with net migration rates influenced by current dynamics.Two hundred and thirty six unique presence points of C. puniceus were correlated with seasonal maximum and minimum temperature data and bathymetry to model the current distribution and predict future distribution changes of the species up until 2030. Eight individual species distribution models were developed and combined into a mean ensemble model using the Biomod2 package. Winter minimum temperature was the most important variable in determining models outputs. Overall the ensemble model was accurate with a true skills statistic score of 0.962. Binary transformed mean ensemble models predicted a northern and southern range contraction of C. puniceus' distribution of 15 percent; by 2030. The mean ensemble probability of occurrence models indicated that C. puniceus' abundance is likely to decrease off the southern Mozambique coastline but remain high off KwaZulu-Natal. The results of the genetic analysis support the theory of external recruitment sustaining the KwaZulu Natal fishery for C. puniceus. While the high genetic diversity and connectivity may make C. puniceus more resilient to disturbances, the loss of 15 percent; distribution and 11 percent; genetic diversity by 2030 will increase the species vulnerability. The decrease in abundance of C. puniceus off southern Mozambique together with current widespread exploitation levels could result in the collapse of the fishery. A single transboundary stock of C. puniceus highlights the need for co-management of the species. A combined stock assessment between South Africa and Mozambique and the development of further Marine Protected Areas off southern Mozambique are suggested as management options to minimise the vulnerability of this species.
Keywords: Sparidae; Fishes -- Indian Ocean; Fish populations; Fishery management; Fish stock assessment -- South Africa; Fish stock assessment -- Mozambique; Overfishing; Habitat conservation; Fishes -- Genetics; Fishes -- Climatic factors; Fishes -- Variation; Fishes -- Migration